2016
DOI: 10.3389/fevo.2016.00135
|View full text |Cite
|
Sign up to set email alerts
|

Status Specific Tailoring of Sperm Behavior in an External Fertilizer

Abstract: Why dominant males experiencing intense sperm competition sometimes show low investments in sperm production is not always obvious. One well-documented example is that of the external fertilizing teleost, the Arctic charr (Salvelinus alpinus), where individuals becoming dominant reduce sperm production and sperm swimming speed in water compared to subordinates. Here, we report how ovarian fluid differentially influences sperm velocity of dominant and subordinate male Arctic charr. That is, sperm from dominant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 61 publications
(99 reference statements)
0
18
0
Order By: Relevance
“…Also, Arctic charr (Salvelinus alpinus) sperm from dominant males had greater motility in ovarian fluid (Egeland et al 2016). This increased mobility could be cryptic female choice, via ovarian fluid, for dominant male sperm or dominant male sperm could simply be better at moving through ovarian fluid (Egeland et al 2016); however, the experiment could not disentangle the two competing hypotheses. Makiguchi et al (2016b) found that ovarian fluid differentially affects the sperm of precocious parr and anadromous masu salmon (Oncorhynchus masu).…”
Section: Post-spawning Sexual Selectionmentioning
confidence: 99%
“…Also, Arctic charr (Salvelinus alpinus) sperm from dominant males had greater motility in ovarian fluid (Egeland et al 2016). This increased mobility could be cryptic female choice, via ovarian fluid, for dominant male sperm or dominant male sperm could simply be better at moving through ovarian fluid (Egeland et al 2016); however, the experiment could not disentangle the two competing hypotheses. Makiguchi et al (2016b) found that ovarian fluid differentially affects the sperm of precocious parr and anadromous masu salmon (Oncorhynchus masu).…”
Section: Post-spawning Sexual Selectionmentioning
confidence: 99%
“…Guarding and synchronized spawning by the dominant male may thus leave fewer unfertilized eggs available for the sneaker males, and the eggs will also be more dispersed and difficult to fertilize. Yet, sperm competition occurs when sneaker males try to fertilize a limited number of dispersed, unfertilized eggs (Birkhead & Møller, ; Egeland, Rudolfsen, Nordeide, & Folstad, ; Sørum et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…This is contrary to Egeland et al () who reported relative sperm velocity and motility as the best predictor of male fertilization success in charr from our study population. In the latter study, the two males whose sperm were competing to fertilize eggs in vitro were caged together for four days prior to fertilizations in order to deliberately produce one dominant male with low sperm velocity and one subordinate male with high sperm velocity (see also Egeland et al, ; Rudolfsen et al, ). This “production” of large differences in sperm velocity might explain the contrasting effects of sperm velocity on paternity in the two studies.…”
Section: Discussionmentioning
confidence: 99%
“…In our studied charr population, 76.5% of the ejaculates experience sperm competition and the mean number of males releasing milt in each spawning event is 2.6, suggesting a high level of sperm competition (Sørum et al, ). Sperm velocity and sperm density differ predictably between males adopting dominant or subordinate spawning strategies; that is, subordinates have more sperm with higher velocity in water, yet lower velocity in OF, than dominants (Egeland et al, ; Rudolfsen et al, ). Additionally, velocity of sperm in ejaculates has also been shown to influence fertilization success under sperm competition (Egeland, Rudolfsen, & JT, Folstad I., ; Liljedal et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation